How Should Law Student Think in Criminal Cases? - Adiyatma, Septhian Eka; Arifin, Ridwan; Ilyasa, Raden Muhammad Arvy; Widyawati, Anis; Rasdi, Rasdi (Law Research Review Quarterly, 2020)
This paper aims to analyze the critical thinking abilities of law students in analyzing criminal law cases related to human rights. This paper uses a survey method where the respondents surveyed were students of the Faculty of Law, State University of Semarang who are actively involved in various student organizations. This research shows that to sharpen the critical thinking skills of law students, encouragement and stimulus are needed in the form of working papers and small groups in the analysis of criminal law cases. In addition, presenting cases in groups allows students to interact intensely and continuously.